Comparison between two insecticide application methods in controlling lesser mealworm beetles in commercial broiler housessser mealworm beetles in commercial broiler houses - Panzardi, Andrea; Nunes, Rogério de Faria; Gaggini, Thais Schwarz; Oliveira, Gustavo Bomfim Alves de; Guimarães, Ednaldo Carvalho; Antunes, Robson Carlos; Silva, Amilton; Rezende, Marcus Luciano Guimarães (Revista de Ciências Agroveterinárias, 2019)
The lesser mealworm control is mostly made by insecticides, as the association of chlorpyrifos, cypermethrin and citronellal. The traditional insecticide application method (TRADM) depends on many liters of water and, with the objective of reducing water consumption, the aim was to compare TRADM with atomizer-equipment method (ATOMM). Four and three houses from farm A and B were used, respectively. Houses 1, 3 and 7 were treated with TRADM (1 liter of insecticide diluted in 500 liters of water) and houses 2, 4, 5 and 6 with ATOMM (1 liter of insecticide diluted in 9 liters of water). Twenty-four hours before and 30 (for farm A) and 45 days (for farm B) after the insecticide application, the number of insects was counted in each house (using 18 mapped traps/house). Farms were not considered different (p>0.05) and comparison was made between the houses. Houses were different (p<0.001) in the pre-treatment count, but they were equal in the second count (p=0.97). The insecticide application increased the number of traps without any insect (p<0.0001). In conclusion, the application method of chlorpyrifos, cypermethrin, and citronellal insecticide using atomizer equipment presented similar results than using the traditional application method. Both methods were effective in reducing the infestation of all houses, not making any difference if the dilution of the product was in 500 liters or in 9 liters of water; thus, it is possible to spend less water to run this management.